Using Modified Genetic Algorithm for Enhancing Network Connections Distribution - Salih Al-Shamery, Eman; A.Rahoomi Al-Obadi, Ali (International Journal of Engineering and Technology, 2018)
In this paper, a developed Genetic Algorithm (dGA) has been proposed as an efficient method to find optimal distribution of network connections. There are many network devices can be used as a terminal station such as computers, hubs, routers or wireless networks. The proposed algorithm depends on the modifying of the traditional genetic algorithm (GA) parameters. The parameters of GA are initial population, encoding, evaluation, crossover, mutation, replacement and stopping criteria. The population consists of many chromosomes, each gene in a given chromosome represent a station of network. The chromosome has fixed length for all population. This paper aims to provide an efficient way to identify the population that gives the best paths for mesh topology network and detect optimal path, at the end the final population preserve only the shorter paths that gives best solution to reach goal.Â Â